El clima urbano en Oporto: oportunidad para repensar la sustentabilidad del territorio y retomar los ritmos de la naturaleza - Monteiro, Ana (2012)
At the end of the century, the city will be the environment of choice for most of world's population to live. Projection gives us the guidelines to reflect and have a vision for the future and try to understand the different forms of domination that man has on the atmosphere, hydrosphere and lithosphere. The city of Porto, Portugal is an excellent case study provides insight adjustment between the timeline, the aspirations of human beings and other ecosystem elements. This paper reflects on the relationship between the characteristics of each of the pieces and the respective urban local and regional climate, to show users or city planners, the importance of adequate and systematic reading when trying to carry out an idea or a project in urban spaces.